The use of transformational-generative theory in the preparation of Arabic learning materials for non native speakers / Bouketir Amel - Bouketir, Amel (2017)
The present study aimed to build a proposed program to improve the learning process of Arabic language for non-native speakers at advanced level, and to achieve that this study was divided into two parts the first part is theoretical aspect, it included four various chapters, it discussed the theoretical framework on the study which presented definition of the general linguistics, applied Linguistics and their relationship for non-native speakers to learn Arabic. Furthermore, the study address the theory of transformational-generative, as the study units and the basics of preparing it is also discussed, then the practical part that contained the proposed program which included seven units each unit included three lessons for a total of twenty-seven lesson and each lesson was crowned by five exercises prepared based on the theory of transformational-generative. This study relied on three bases: generative grammar, syntax and the six transformational elements. The study also presented with a proposed program a guideline for teachers to help them implement the program using suggested educational ways and methods. To achieve the objectives of study this research applied descriptive approach through the induction and deduction and the practical approach in the practical part of the study. Findings of the study showed that the theory of transformational-generative can benefit the non-native speakers in the process of learning, and it proved that through the construction of the proposed program in the light of theory of transformational-generative based on the three foundations of the theory mentioned which are: limited grammars, parts of the phrase and six elements of conversion. Furthermore, it is found that the reliance on generative theory in the process of learning Arabic by non-native speakers makes the student a positively effective to get the role to teach Arabic, since it depends on the mental and intellectual abilities of student, it therefore provide an interpretation of linguistic facts. In addition, this study proposed a program based on theory of transformational-generative to contribute to the development of the process of learning Arabic by non-native speakers, and we think it is the first step to move in such a direction of these studies. At the end, we hope that this study presented even if a little contribution in the field of learning process i.e., daad language the language of the Qur'an to non-native speakers.